2007
DOI: 10.4049/jimmunol.179.1.372
|View full text |Cite
|
Sign up to set email alerts
|

Gliadin Regulates the NK-Dendritic Cell Cross-Talk by HLA-E Surface Stabilization

Abstract: We analyzed the autologous NK cell interaction with gliadin-presenting dendritic cells. Gliadin is the known Ag priming the celiac disease (CD) pathogenesis. We demonstrate that gliadin prevents immature dendritic cells (iDCs) elimination by NK cells. Furthermore, cooperation between human NK cells-iDCs and T cells increases IFN-γ production of anti-gliadin immune response. Gliadin fractions were analyzed for their capability to stabilize HLA-E molecules. The α and ω fractions conferred the protection from NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 60 publications
2
31
0
Order By: Relevance
“…This may result in direct stimulation of NK cells present in the lamina propia by gliadin or APCs [38,39]. It has also been suggested that gluten peptides might be presented by DCs sampling the intestinal lumen [40], which may increase the crosstalking with NK cells [14], thus making it possible for gliadin to activate NK cells even in the absence of a leaky gut epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may result in direct stimulation of NK cells present in the lamina propia by gliadin or APCs [38,39]. It has also been suggested that gluten peptides might be presented by DCs sampling the intestinal lumen [40], which may increase the crosstalking with NK cells [14], thus making it possible for gliadin to activate NK cells even in the absence of a leaky gut epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Gliadin fragments have also been shown to stimulate TLR4 and activate innate cells such as monocytes, macrophages, and DCs [13], and to regulate the NK-cell DC crosstalk by stabilizing HLA-E on the cell surface [14]. The exact role of dietary gluten and gliadin fragments in NK-cell activity and T1D has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, gliadin enhanced the maturation of blood-derived immature DCs in all subjects irrespective of their genotype or of the presence of celiac disease, although gliadin-stimulated DCs from untreated celiac patients showed increased stimulation of autologous T cells compared with the other groups (110). Furthermore, gliadin plays a detrimental role in the regulation of NK cell-DC interactions, as it may switch the NK cell-DC cross-talk from a tolerogenic pathway (based on immature DC elimination) to a pathogenic one in which gliadin inhibits NK cell cytotoxicity against immature DCs via the CD94/ NKG2A pathway (111).…”
Section: Figurementioning
confidence: 99%